2019
DOI: 10.1038/s41598-019-47706-3
|View full text |Cite
|
Sign up to set email alerts
|

Unnatural spirocyclic oxindole alkaloids biosynthesis in Uncaria guianensis

Abstract: Spiro-oxindole scaffolds have been studied due to their promising therapeutic potential. In the Amazon rainforest there are two important Uncaria species known as “cat’s claw”, which biosynthesize spirocyclic oxindole alkaloids; Uncaria tomentosa (Willd. ex Schult.) DC. and Uncaria guianensis (Aublet) Gmell. We carried out a precursor-directed biosynthesis approach with U. guianensis and successfully obtained oxindole a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…It is important to highlight that all plants have grown healthy, without visible physiological change, which means that the unnatural precursor was not toxic for the plantlets. A methanolic extract from fresh shoots of T. catharinensis was prepared after 30 Our results showed that PDB strategies using analogue precursor successfully produced unnatural alkaloids in T. catharinensis.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…It is important to highlight that all plants have grown healthy, without visible physiological change, which means that the unnatural precursor was not toxic for the plantlets. A methanolic extract from fresh shoots of T. catharinensis was prepared after 30 Our results showed that PDB strategies using analogue precursor successfully produced unnatural alkaloids in T. catharinensis.…”
Section: Resultsmentioning
confidence: 91%
“…Due to the importance of natural product analogues, many strategies for modifying natural products have been explored in order to obtain "new-to-nature" molecules [29]. Recently, we have demonstrated that the biosynthesis of fluorinated and methylated analogues of oxindole alkaloids in Uncaria guianensis plantlets by precursor-directed biosynthesis (PDB) is a viable and efficient bioprocess, and this approach is unusual using plants [30]. The successful incorporation of unnatural precursors in the biosynthetic route of a given natural product can lead to the formation of an analogue that can be more biologically important than the natural product itself.…”
Section: Introductionmentioning
confidence: 99%
“…J.F.Gmel. It was determined that the formation of the oxindole moiety proceeds along a pinacol-pinacolone rearrangement reaction from an indole precursor [57]. The oxindole moiety is comprised of a benzene ring fused with a pyrrole ring, substituted at C-2 with a carbonyl [55].…”
Section: Oxindole Alkaloidsmentioning
confidence: 99%
“…The biosynthesis as well as synthesis of other representatives of this compound class is well studied (see e.g. Lopes et al 2019;Martin et al 1991). Therefore, similar work is necessary to investigate the proposed javaniside biosynthesis in Palicourea in the context of the general 2-oxindole alkaloids biosynthetic pathways.…”
Section: Javanisidementioning
confidence: 99%